SUPPLY CHAIN MANAGEMENT IMPLEMENTATION TO ENHANCE FIRM’S COMPETITIVE ADVANTAGE - Putra, Yuniarti Hidayah Suyoso (IQTISHODUNA, 2012)
Rapidly changing business environment has led to the change of supply change management (SCM) implementation. This paper attempts to discuss the benefits of SCM and how the companies manage it in order to maintain their competitive advantage. Illustrations from several companies are included. To achieve sustainable competitive advantage, five basic steps in supply chain management i.e. plan, source, make, deliver and return as discussed earlier should be conducted and evaluated carefully and continuously. SCM should take into consideration the choice of strategic partnerships not only based on the most efficient and effective cost structure but also the legal aspect of the supplier to avoid the company being shut down by the government. Trust and relationships with the suppliers should be maintained and finally, the technology innovation in SCM of a company should be developed more advanced, compared or combined with other companies to sustain competitive advantages.